UTILIZATION OF TORAY FLY ASH AS FILLER SUBSTITUTION IN THE HOT ROLLED SHEET-WEARING COURSE (HRS-WC) MIXTURE - F. Candra; L. B. Suparma (Journal of the Civil Engineering Forum, 2011)
In road construction materials, the utilization of fly ash as additive materials is limited and also small in quantity, while the disposal of fly ash is quite high. An abundance of fly ash can be found at PT Toray Company in Jakarta and Surabaya. Toray fly ash is disposed coal ash resulting from coal-fired electricity generating power plants. Toray fly ash in this research is used as substitute mineral filler in asphalt paving mixtures. Research on utilization of Toray fly ash as filler is conducted in the Hot Rolled Sheet – Wearing Course Mixture.  Filler content in the HRS –WC mixture is 9%. Variations of Toray fly ash in the mixture tested are 0%, 25%, 50%, 75%, 100% and the variations of asphalt content are 6%, 6.5%, 7%, 7.5%, 8%. Marshall test is  performed to determine the Optimum Asphalt Content  and Marshall Stability, Indirect Tensile Strength (ITS) test and Tensile Strength Ratio (TSR) to select the optimum Toray fly ash utilization in the mixture based on the moisture susceptibility of specimens. The research results show that in variations of 0%, 25%, 50%, 75% and 100% Toray fly ash in the HRS-WC Mixture, the Optimum Asphalt Contents are at 6.8%, 7.0%, 7.0%, 7.1% and 7.6%  and Marshall Stability values of the variations are 1649 kg, 1541 kg, 1568 kg, 1678 kg, 1718 kg respectively. TSR values in variations of Toray fly ash are 98.32%, 90.28%, 89.38%, 87.62%, 64.71% respectively, with Minimum TSR value required is 80%. Based on the overall parameters, the optimum Toray fly ash utilization in the HRS-WC Mixture recommended is 75% of Toray fly ash at 7.1% Optimum Asphalt Content.